Keuneunong: Learning from Authority - Ezra M. Choesin; Hafiz Awlia Ramadhan (Antropologi Indonesia, 2015)
Knowledge systems have been the focus of much anthropological work, although there have been shifts in definitions and perspectives. One aspect of knowledge is that it is learned, mostly informally through a process of trial and error. The keuneunong is one such knowledge system, known to be distributed among Acehnese farmers and used mainly to determine planting schedules and crop selection. Although it serves as a guide for agricultural activities, most farmers do not understand it fully, and leave its interpretation to an authority known as the kejrun blang. Research for this article was conducted in Mane, Nanggroe Aceh Darussalam. The findings suggest that the process of trial-and-error learning among farmers is hindered by authority, and that transmission of knowledge of the essence of keuneunong does not occur.Key words: keuneunong, knowledge, learning